Dictionary of education - Dewey, John (Philosophical Library / Open Road Integrated Media, 2015)
Dictionary of Education is a comprehensive resource on John Deweys approach to education. With smart, concise definitions pertaining to Deweys philosophies, editor Ralph B. Winn has constructed a classic dictionary and indispensable tool for anyone who wants ready access to Deweys most incisive thought on crucial points in the study of education.